Description of the Physical Condition of the House and the Presence of Staphylococcus aureus in the Toddler's House with Pneumonia in Pakusari District, Jember Regency - Bayhaqi, Rendy Achmad; Ma'rufi, Isa (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2024)
Pneumonia is a significant health issue, causing both long-term and short-term mortality across all age groups globally. The Pakusari District notably has a high rate of pneumonia among toddlers. According to data from the Jember District Health Office, in 2021, there were 88 cases of toddler pneumonia in Pakusari District. Preventive measures against pneumonia include addressing its various risk factors. This study employed a quantitative descriptive research design, focusing on 23 homes with toddlers suffering from pneumonia in Pakusari District, Jember Regency, from September to November 2023. A sample of 10 houses was selected based on Gay and Diehl's (1992) theory using systematic random sampling. The findings were presented in text and tables. The study revealed that 60% of the houses had good physical conditions, while 40% had poor physical conditions. Additionally, Staphylococcus aureus was not found in most houses, with only 10% of the homes having the bacteria present. The homes with Staphylococcus aureus typically had physical conditions that did not meet health standards, including issues with ceilings, floors, ventilation, kitchen smoke holes, lighting, temperature, humidity, and occupancy density. The study suggests that the Pakusari Health Center should enhance health promotion efforts and optimize sanitation clinics. The Jember District Health Office could implement programs to increase the number of healthy homes, such as plastering programs and providing glass roof tiles. The community should regularly clean their houses and ensure adequate lighting to improve overall health conditions.